Height matters: The experiences of very tall young British adults in relation to managing everyday occupations. Issue 2 (3rd April 2019) - Booth, Julie; Rihtman, Tanya; Leddington Wright, Sheila; Taylor, M. Clare; Price, Michael
ABSTRACT: Adults with a very tall stature (above the 97 th percentile for height) encounter challenges with engagement in everyday occupations. Conversely, work-related opportunities and benefits for the taller worker have been identified. This interpretive phenomenological study captured the occupational narratives of very tall young British adults in relation to how the diversity of their stature affects participation in everyday occupations. Eight participants between the ages of 18 and 40 years engaged in an individual interview to share their experiences. Analysis of the data produced two super-ordinate themes, 'Fitting into an average height world' and 'Playing to Strengths'. Challenges to occupational engagement and performance have necessitated strategies involving compromise. In some instances, reduction in occupational choice has occurred because tall stature has precluded engagement. Conversely, occupations have been chosen by participants for which height is an advantage, thereby making the most of a stature that cannot be changed. Findings imply that very tall stature affects occupational choice, which in turn shapes identity.